Chomsky's Transformational Linguistic Theory in Writing Skill at Islamic Senior High School: Transforming Language Learning Pedagogy - Wildana Wargadinata; Lisa Khillatur Risalah; Ulul Elmi; Iffat Maimunah; Suo Yan Mei (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2021)
This research aimed to determine the implementation's effectiveness as supporting and inhibiting factors of Chomsky's Transformational Linguistic Theory in Writing Skill implementation. The data were collected through interviews, observations, and tests. The results of this study are: 1) the researchers obtained the difference in scores between the pretest and posttest of the control class and the experimental class. 2) there were five supporting factors and three inhibiting factors in learning maharah kitabah at MA Muallimat Malang Indonesia. The supporting factors are: 1) the transformation of sentences is easy to understand, 2) students have the ability of basic Arabic rules, 3) students can write Arabic, 4) enthusiasm in participating in learning activities, 5) availability of sufficient media for learning. Meanwhile, the inhibiting factors are: 1) the difficulty of students distinguishing mudzakkar and muannats,2) only a few materials limits transformation, 3) some students do not like to learn Arabic.